Epitaxial Growth Of Iii-V Nitrides Based Light Emitting Diodes By Metal Organic Chemical Vapor Deposition - Samsudin, Muhammad Esmed Alif (2023)
This research aims to improve the performance of indium gallium nitride (InGaN) based LEDs and to demonstrate a working aluminum gallium nitride (AlGaN) based LEDs through metal organic chemical vapour deposition epitaxy. The effect of gallium nitride (GaN) nucleation growth temperature, superlattice period, and indium composition on InGaN based LED performance was studied. It was found that growing GaN nucleation at 570°C reduced threading dislocations (TDs) in the overgrown GaN layer (which served as the LED base layer). At 570°C nucleation, larger 3D growths (islands) formed, promoting dislocation inclination, and thus reducing TDs. Subsequently, 20 periods of In0.04Ga0.96N/GaN SLs led to reasonable V-pits size. This increased holes injection into the multiquantum well and hence, improved the LED performance. This research also attempted to find out factors which limit the use of GaN substrates in InGaN based LEDs development over sapphire substrates, particularly pattern sapphire substrate (PSS), which is widely used in many studies, including in this research.